0.6(1-6z)=-6

Simple and best practice solution for 0.6(1-6z)=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.6(1-6z)=-6 equation:



0.6(1-6z)=-6
We move all terms to the left:
0.6(1-6z)-(-6)=0
We add all the numbers together, and all the variables
0.6(-6z+1)-(-6)=0
We add all the numbers together, and all the variables
0.6(-6z+1)+6=0
We multiply parentheses
-3.6z+0.6+6=0
We add all the numbers together, and all the variables
-3.6z+6.6=0
We move all terms containing z to the left, all other terms to the right
-3.6z=-6.6
z=-6.6/-3.6
z=1+3/3.6

See similar equations:

| ​3​​2​​n+54=32 | | 0=-0,1x²+0,9x+1 | | (3x+8)4+6=6(2x+17) | | (2x+28)=(4x+5) | | 2(4-x)=3(3x-2) | | 3/x+2+3/x-2=2 | | 4(6r+3)+2(r+2)=4, | | 4r+12=4 | | (=10+5z)⋅2+5(z+4)= | | 6=2m-8 | | F(2)=3x^2+4x-4 | | 9w=57.78 | | 27+c=180+3 | | ×=1000.7x³+x²-10 | | 200+50=a+250 | | 0.7x³+x²-10x=100 | | x-27=100 | | 2x+12=57 | | (3-2X)+3(1-4X)-4(1-5X)=1(2-3x) | | h+78=141 | | 0.03x=250 | | 2=8x-4x-7x | | -9/10(x+8)=18 | | n+4=11.n | | F(x)=-7x^2+5x | | v/18=2/3 | | 2(3x+5)=50 | | j/13=16 | | .8(-2x-1)=24 | | 8c=11.2 | | 99y-2y=5 | | 7x+3(2x-6)=34 |

Equations solver categories